Fabrication of Transparent Dysprosium Aluminum Garnet (Dy3Al5O12) Ceramics via a Solid‐State Reaction Method. Issue 6 (28th April 2015) - Hu, Song; Qin, Xianpeng; Lu, Chunhua; Zhou, Guohong; Xu, Zhongzi; Wang, Shiwei; Reimanis, I.
<x xml:space="preserve">Abstract</x> Polycrystalline, transparent Dy3Al5O12 ceramics were firstly fabricated by a solid‐state reaction method using high‐purity Dy2O3 and Al2O3 powders. The fully dense Dy3Al5O12 ceramic with an average grain size of less than 10 μm was obtained by vacuum sintering at 1820°C for 6 h. The in‐line transmittance of the optimized sample reaches 80% in the visible region. Scanning electron microscopy reveals that no secondary phases and almost no pores are observed at grain boundaries or triple junctions, and the fracture mode of the ceramic is mainly transgranular. The Dy3Al5O12 ceramic is promising for magneto‐optical applications. Verdet constant of the Dy3Al5O12 transparent ceramic is as high as −0.41 min·(Oe·cm)−1.